Enhancing the Effect of Combination Therapy with the PARP Inhibitor Talazoparib and ionizing Radiation on Melanoma Cell Lines - Proebstle, Stephanie; Jost, Tina; Buerkel, F.; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36488

Investigation of a radioprotective Effect of the Kinase Inhibitor Palbociclib on Melanoma Cells in a 3D Cell Culture Model - Jost, Tina; Buerkel, F.; Proebstle, Stephanie; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36487

Kinase Inhibitor Palbociclib shows differential Effects upon Irradiation on Normal Tissue and Cancer Cell Lines - Jost, Tina; Proebstle, Stephanie; Buerkel, F.; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36486

PARP Inhibitors Talazoparib and Niraparib Sensitize Melanoma Cells to Ionizing Radiation - Jonuscheit, Stephanie; Jost, Tina; Gajdošová, Fritzi; Wrobel, Maximilian; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (Genes, 2021)
(1) Background: Niraparib and Talazoparib are poly (ADP-ribose) polymerase (PARP) 1/2 inhibitors. It is assumed that combining PARP inhibitors with radiotherapy could be beneficial for cancer treatment. In this study, melanoma cells were treated with Niraparib and Talazoparib in combination with ionizing radiation (IR). (2) Methods: The effects of Talazoparib and Niraparib in combination with IR on cell death, clonogenicity and cell cycle arrest were studied in healthy primary fibroblasts and primary melanoma cells. (3) Results: The melanoma cells had a higher PARP1 and PARP2 content than the healthy fibroblasts, and further increased their PARP2 content after the combination therapy. PARP inhibitors both sensitized fibroblasts and melanoma cells to IR. A clear supra-additive effect of KI+IR treatment was detected in two melanoma cell lines analyzing the surviving fraction. The cell death rate increased in the healthy fibroblasts, but to a larger extent in melanoma cells after combined treatment. Finally, a lower percentage of cells in the radiosensitive G2/M phase is present in the healthy fibroblasts compared to the melanoma cells. (4) Conclusions: Both PARP inhibitors sensitize melanoma cells to IR. Healthy tissue seems to be less affected than melanoma cells. However, the great heterogeneity of the results suggests prior testing of the tumor cells in order to personalize the treatment.
CRIS-Team Scopus Importer:2021-06-18
Keywords: ionizing radiation; kinase inhibitors; PARP

Tumor-specific Toxicity to malignant Melanoma Cells by the dual DNA-PK and mTOR Inhibitor CC115 in Combination with ionizing Radiation - Burkel, F.; Jost, Tina; Proebstle, Stephanie; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (2018)
EVALuna2:36482